Anisotropic valence band dispersion of single crystal pentacene as measured by angle-resolved ultraviolet photoelectron spectroscopy. Issue 20 (29th October 2018) - Nakayama, Yasuo; Hikasa, Masataka; Moriya, Naoki; Meissner, Matthias; Yamaguchi, Takuma; Yoshida, Koki; Murata, Mimi; Mase, Kazuhiko; Ueba, Takahiro; Kera, Satoshi
Abstract: Abstract : Electronic structures of single crystal pentacene are of great interest for the elucidation of charge carrier transport in organic semiconductor materials. Experimental observation of valence band dispersion was recently achieved on single crystal samples of pentacene; however, its intrinsic properties are still unresolved because past experiments were performed on specimens with surface oxides formed by exposure to the ambient atmosphere. In this work, X-ray photoelectron spectroscopy (XPS) and angle-resolved ultraviolet photoelectron spectroscopy (ARUPS) were conducted on single-crystal pentacene samples prepared without ambient exposure. The XPS results confirmed the reduction of the abundance of oxide impurities on the present samples. The ARUPS measurements clearly resolved the valence band structures of the single-crystal pentacene in four symmetry directions of the surface Brillouin zone, indicating anisotropy of at least a factor of 2.4 for the intermolecular transfer integral and hole effective mass at the valence band maximum.